GE_GERICHTE P/18284/2018 vom 5. Mai 2022 - GE Cour de justice (2022)
ORDONNANCE DE CLASSEMENT;FRAIS DE LA PROCÉDURE;DÉPENS;IMPUTATION;PLAIGNANT;ÉQUITÉ | CPP.427.al2; CPP.426.al2; CPP.432.al2; CPP.429.al1.leta; CC.4